Antimicrobial activity of fungal endophytes from Vaccinium dunalianum var. urophyllum - Xin, Tong; Xiao, Ye Shen; Cheng, Lin Hou (Penerbit Universiti Kebangsaan Malaysia, 2018)
Fungi associated with Vaccinium species play important roles in plant growth and disease control, especially in the final blueberry production. Vaccinium dunalianum var. urophyllum (Ericaceae) is a well-known medicinal plant in Southern China used to treat inflammation and microbial infections. The endophytic fungi from these plants are therefore anticipated as potential new sources of antimicrobials. In this report, the inhibitory effects of endophytes against clinical bacteria and yeast were comprehensively screened and 11 isolates indicated high bioactivity by the agar diffusion method. The corresponding crude extracts of these fungi under submerged fermentation also demonstrated distinct differences and n-butyl alcohol displayed the lowest extraction efficiency among the extracts. The ethyl acetate and dichloromethane extracts of filtrates from the Colletotrichum sp. VD001, Epicoccum nigrum VD021 and E. nigrum VD022 strains displayed good properties against pathogenic microorganisms according to disc diffusion assays and minimal inhibitory concentration (MIC). This study is the first indicating that cultivable endophytic fungi associated with blueberry plants produce potential compounds against clinical pathogens.